IoT-Driven Solutions for Improved Plant Care in Terrariums - Diva Septiawan; Misbahuddin; Wiriasto, Giri Wahyu (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2025)
The rapid advancement of Internet of Things (IoT) technology has revolutionized various sectors, including smart agriculture. This study explores an IoT-driven solution to enhance plant care in terrariums by automating maintenance and optimizing growth conditions. The proposed system monitors key environmental parameters temperature, humidity, and soil moisture while automating irrigation using an ESP32 microcontroller, DHT11 and YL-69 sensors, a relay, and a mini DC pump. An Android application, developed with Android Studio and Arduino IDE, integrates the system via Firebase for real-time data access. A 14-day observation of Rombusa plant growth revealed that the optimal soil moisture level ranges between 60%–70%, averaging 65%. The findings confirm that IoT-driven plant care enhances growth efficiency and simplifies maintenance, offering a more effective alternative to traditional methods.